Synthesis and characterization of organic dyes containing 4,5-diazafluorene as efficient sensitizers for dye-sensitized solar cells - Erden, Ibrahim; Cebeci, Caner; Kilicarslan, Fatma Aytan (TAYLOR & FRANCIS LTD, 2017)
Two dyes which are 4,5-diazafluoren-9-one-derived diimine ligands and their corresponding Ru(II) bipyridine complexes were synthesized. The structures of all compounds were determined by FTIR, UV-Vis, H-1-NMR, C-1-NMR, and MS spectroscopic data. The photovoltaic and electrochemical properties of these compounds were investigated and the applicability in DSSCs as photosensitizers was studied. The photovoltaic cell efficiencies (PCE) of the devices were 0.36-1.26% under simulated AM 1.5 solar irradiation of 100 mW/cm(2), and the highest open-circuit voltage (V-oc) reached 0.34 V. When comparing the photovoltaic performance of DSSC devices, efficiency increases L2 < L2-Ru < L1 < L1-Ru. The PCE value of 1.26% was obtained with a DSSC based on L1-Ru under AM irradiation (100 mW/cm2). DSSC based on L1-Ru produced efficiency of 1.26%, whereas DSSC-based L1 exhibited the device performance with efficiency of 0.84% under illumination. These results show that the availability of a p-conjugated bridge and a richer electron donor for photovoltaic performance of the DSSC provides increased efficiency. [GRAPHICS] .
Keywords: DSC; 4,5-diazafluorene; Schiff base; ruthenium complexes; PI-A DYES; PHOTOVOLTAIC PROPERTIES; ACCEPTOR; BRIDGE; LIGAND; DONOR; Chemistry